ChemInform Abstract: Mono and Difluorination of Centers α to Sulfonates and Phosphonates Using AcOF. Issue 21 (2nd May 2013) - Vints, Inna; Gatenyo, Julia; Rozen, Shlomo
Abstract A general method for the selective introduction of one or two fluorine atoms in α‐position to a sulfonate or phosphonate moiety in very short time is described.